(untitled) (Tzintzun, Revista de Estudios Históricos, 2024)
This article addresses the issue of the primary titles of the indigenous communities of the Sierra P’urhépecha, in the state of Michoacán. The P’urhépecha perspective regarding their own pictographic and alphabetic documents is particularly exposed, with greater attention to the definitions of the documents from the P’urhépecha language. The concepts of k’uirakua are analyzed, the case of the Lienzo de Comachuen, echeri míntakua, atánskatecha, eránhikua p’itákatecha, kuirútsikatecha, karánskata p’itákatecha, mienskuecha, uaripitarakuecha and kuapitarakurhikuecha, framed in the notion of tua anapu karákatecha, ancient writings or old documents.